How Do Anchors' Characteristics Influence Consumers' Behavioural Intention in Livestream Shopping? A Moderated Chain-Mediation Explanatory Model - Zhu, Liangjie; Li, Huiyao; Nie, Kun; Gu, Chunmei (Frontiers in Psychology, 2021)
Livestream shopping has become the focus of current marketing practises, while theoretical research on it is still in initial stages. Thus, from the para-social interaction (PSI) theory perspective, this study draws on cognitive–affective system theory as an analytical framework to explore internal mechanisms of how anchors' characteristics influence consumer behavioural intentions in livestream shopping while considering the characteristics of consumer online interaction propensity. We conducted a survey questionnaire with a sample of 355 consumers who experienced livestream shopping and used structural equation modelling to assess their behavioural intentions. Our results reveal that anchors' physical attractiveness, social attractiveness, and professional ability influence consumers' intentions to follow the authors' suggestions and recommend anchors to others during live streams. PSI and affective trust in anchors are the chain-mediation mechanisms. Furthermore, consumers' online interaction propensity positively moderates the influence of anchors' characteristics on PSI and plays a moderating role on the whole chain mediation. However, this only affects anchors' physical attractiveness and social attractiveness while exert no effect on anchors' professional ability. This study advances the theoretical research on livestream shopping and provides practical inspiration for managers to develop more targeted livestream marketing strategies.